2023
DOI: 10.21203/rs.3.rs-2649049/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The CpG-dependent plant immune response to self-DNA triggers defence hormone signalling and improves fitness

Abstract: The accumulation of DNA in the cytoplasm or extracellular space is a signal of danger. Plants respond to this signal with a self/non-self-specific activation of early immune signalling events. Here, we asked whether this specificity translates to fitness-relevant resistance to natural enemies. We treated common bean (Phaseolus vulgaris) plants with self-DNA and with non-self-DNA from other plant species. Self-DNA treatment induced jasmonic acid and decreased feeding by a chewing herbivore (Spodoptera frugiperd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…The levels of JA peaked at 30 min and those of SA at 24 h ( Figure 2 ; Supplementary Figure S3 ). Subsequent treatments revealed self/nonself-specific effects of DNA on H 2 O 2 and both hormones and in all cases, strongest effects were triggered by self-DNA ( Figure 2 ), similar to earlier observations, although with minor differences between species ( 20 22 , 26 , 35 , 36 ). The response times and levels reached by the three signals fall clearly within the standard kinetics of the three signals ( 119 121 ).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The levels of JA peaked at 30 min and those of SA at 24 h ( Figure 2 ; Supplementary Figure S3 ). Subsequent treatments revealed self/nonself-specific effects of DNA on H 2 O 2 and both hormones and in all cases, strongest effects were triggered by self-DNA ( Figure 2 ), similar to earlier observations, although with minor differences between species ( 20 22 , 26 , 35 , 36 ). The response times and levels reached by the three signals fall clearly within the standard kinetics of the three signals ( 119 121 ).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the authors used the same methyltransferase in combination with restriction enzymes to corroborate the methylation of natural herring DNA and thereby could attribute the lower ROS-inducing activity of herring DNA to a TLR9-like mechanism that requires unmethylated CpG motifs ( 9 ). Similarly, a recent study using the same three enzymes to generate DNA free of unmethylated CpG motifs from naturally methylated DNA of common bean and observed that any enzymatic manipulation decreased the H 2 O 2 -inducing properties as compared to the natural self-DNA, with no detectable differences among fragments with completely methylated CpG motifs and fragments in which all unmethylated CpG motifs had been cleaved enzymatically ( 36 ). These results would be consistent with a mechanism in which DNA triggers a partial induction of H 2 O 2 that is independent of CpG-methylation whereas the full response requires additional activation by unmethylated CpG motifs ( 36 ).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations